Characterization of reduced graphene oxide/activated carbon-based electrode containing mixing CMC-SBR binder and application in supercapacitor - Mohd Abid, Mohd Asyadi Azam; Abdul Aziz, Mohd Fareezuan; Tunku Adaham, Tunku Aidil Ilham; Safie, Nur Ezyanie; Mupit, Muazzin; Takasaki, Akito (Penerbit UTM Press, 2022)
In this work, variation of mixing a combination of carboxymethylcellulose (CMC) and styrene-butadiene rubber (SBR) as both used as the binder in the electrode has been studied. The purpose of using CMC-SBR as the binder in the electrode is to achieve a high supercapacitor performance. The electrode preparation has been carried out by mixing the reduced graphene oxide (rGO) and activated carbon (AC) in a blender. The binder preparation started by dissolving the CMC and SBR in the deionized water using a clean glass container. Then, rGO/AC has been stirred with the CMC-SBR for 60 minutes until a homogenous slurry formed. All electrodes have been characterized with Raman spectroscopy. The electrochemical tests such as cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) for all electrode compositions were performed. The electrode with 4:6 (in weight percentage) of CMC-SBR shows the highest specific capacitance (Csp) of 59.65 F g-1 (CV scan rate of 1 mV s-1) and 12.82 F g-1 from GCD test. This confirmed that the electrode containing 4 wt.% of CMC and 6 wt.% of SBR resulting in the best composition, which is reliable and practical for the supercapacitor application.